2018
DOI: 10.1073/pnas.1711335115
|View full text |Cite
|
Sign up to set email alerts
|

Foxp1 controls mature B cell survival and the development of follicular and B-1 B cells

Abstract: SignificanceMany patients with B cell lymphoma carry alterations in the gene coding for the transcription factor Foxp1. High Foxp1 expression has been linked to poor prognosis in those malignancies; however, the physiological functions of Foxp1 in mature B cells remain unknown. By employing genetic mouse models, we show that Foxp1 deletion results in reduced B cell numbers and impaired antibody production upon T cell-independent immunization. Foxp1-deficient mature B cells are impaired in survival and exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 42 publications
(50 reference statements)
5
22
0
Order By: Relevance
“…However, we observed defects in both T-independent and -dependent immunization, which we traced to faulty CSR and GC formation. Finally, both in this study and previously in human DLBCL (23), we confirmed the observation of Patzelt et al (95) of defective expression of prosurvival BCL-2 family members, some of which we showed by ChIP-seq to be direct in human cell lines. In addition to survival, our RNA-seq, GSEA, and ChIP-seq analyses revealed critical FOXP1 target genes regulating GC biology, CSR, PB-to-PC transition, and cytokine production.…”
Section: Convergent Analyses Of Foxp1 B Cell Biologysupporting
confidence: 92%
See 2 more Smart Citations
“…However, we observed defects in both T-independent and -dependent immunization, which we traced to faulty CSR and GC formation. Finally, both in this study and previously in human DLBCL (23), we confirmed the observation of Patzelt et al (95) of defective expression of prosurvival BCL-2 family members, some of which we showed by ChIP-seq to be direct in human cell lines. In addition to survival, our RNA-seq, GSEA, and ChIP-seq analyses revealed critical FOXP1 target genes regulating GC biology, CSR, PB-to-PC transition, and cytokine production.…”
Section: Convergent Analyses Of Foxp1 B Cell Biologysupporting
confidence: 92%
“…However, by employing T1 stage deletion with Cd21-cre, we were able to bypass the pro-B cell block (which led to loss of FO B cells in the periphery and peritoneal cavities) to identify an additional, significant reduction in Bregs. As with Patzelt et al (95), we found Foxp1-deficient B cells to be impaired in survival without significant consequence on proliferation (particularly following stimulation with anti-IgM). However, we observed defects in both T-independent and -dependent immunization, which we traced to faulty CSR and GC formation.…”
Section: Convergent Analyses Of Foxp1 B Cell Biologysupporting
confidence: 89%
See 1 more Smart Citation
“…In fact, Foxp1 directly represses p53-dependent regulatory proteins in neoplastic B-cells, suggesting a strong role in immune modulation [56]. As we currently understand normal anti-cancer responses, a functional immune system is a key component that suppresses cancer [57][58][59]: Foxp1 controls mature B-cell survival and development, and is a regulator for CD4+ T cells [60,61]. Thus, it is also likely that Foxp1 is an essential component that controls the lymphoid immune system, and thereby a modulator of tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…2e). Similarly, metacluster 25 consists of 33 units and contains 151 genes enriched in 24-hour cells such as Mier1 and Foxp1, which has been shown to control mature B-cell survival in mice 26 (Fig. 2e).…”
Section: Identification Of Dynamic Gene Expression Metaclustersmentioning
confidence: 99%